PENGARUH KEMAMPUAN PEMAHAMAN KONSEP TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA MATERI PERKALIAN SISWA KELAS IV UPT SD NEGERI 19 GRESIK - Aprilindah Rahmawati (CV. Adiba Aisha Amira, 2025)
The aim of this research was to determine the ability to understand concepts and solve mathematical problems in multiplication material for class IV students at UPT SD Negeri 19 Gresik. This research also aims to determine the effect of the ability to understand concepts on the ability to solve mathematical problems in multiplication material for class IV students at UPT SD Negeri 19 Gresik. The method used in this research is ex-post facto with a quantitative approach. This ex-post facto research examines cause-and-effect relationships that are not manipulated or treated (designed and implemented) by researchers. This research was conducted at UPT SD Negeri 19 Gresik from November to December 2023 with research subjects being class IV students at UPT SD Negeri 19 Gresik with a total of 32 students. The results of the research carried out were the concept understanding ability of class IV students at UPT SD Negeri 19 Gresik with a percentage of 85.47% in the good category. The problem solving ability of class IV students at UPT SD Negeri 19 Gresik with a percentage of 56.47% in the poor category. The results of simple linear regression analysis of the influence of concept understanding ability on problem solving ability was 25.7%.